Desingning A School Climate Supervision Based on Organizational Culture and Leadership to Improve Professional Competence of Junior High School Teachers in District of Sawahlunto - Hadiyanto Hadiyanto; Yanti Fitria; Sulastri Sulastri; Asril Asril; Velnika Elmanisar; Dinda Syahfitri; Rizki Yatul Hanifah (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2026)
This study aims to develop a school supervision model based on organizational culture and leadership to enhance the professional competence of junior high school teachers in Sawahlunto. The study employed a developmental approach comprising literature review, initial condition mapping, model development, and limited trial implementation. Data were collected through observations, interviews, and questionnaires from 31 teachers and 3 school principals. The findings indicate that current supervision practices are predominantly administrative and mechanistic, providing limited empowerment for teachers as learning agents. The developed supervision model integrates three core elements: Minangkabau-based organizational culture, inspirational and participatory leadership, and reflective-participatory supervision. Implementation of the model demonstrated a 15–20% improvement in teachers’ professional competencies, particularly in lesson planning, use of educational media and technology, and assessment practices. The study highlights that effective supervision must be contextual, empowering, and integrated with school culture and leadership. The proposed model offers a strategic alternative for strengthening teacher professionalism, improving school climate, and promoting participatory school management reform.